Problem prozodične analize spontanega govora - Vitez, Primož (Jezik in slovstvo, 2004)
The bases for a linguistic analysis of spontaneous speech are necessarily correlated to the comprehension of the role played by the subject in making the utterance. The process of making an utterance reveals the fundamental question concerning the subject, which is projected in the utterance, while atthe same time the act of speech completely determines the speakerćs subjective traits. In this sense spontaneous speech is the most common and typical linguistic manifestation, usually occurring in the similarly typical position of an exchange between two subjects. Firstly, the article outlines a historical background and theoretical framework of linguistic speech analysis,while in its analytical, core part it offers one of the possible methodological solutions for the research of spontaneity in the speech act. The methodology is based on the new classification of the basic units of speech, taking into account the principal features of fragmentation and redundancy in spontaneous speech.
Keywords: Slovene; slovenščina; prozodija; govor; spontani govor; linguistics; lingvistika